Differentiation and morphogenesis of Triatoma infestans (Klug 1834) female gonads. I - Post embryonic development - Ibáñez, Cecilia I. (2004)
The post-embryonic development of the female gonads in Triatoma infestans (Hemiptera, Heteroptera), insects of importance in health affairs as harbors and vectors of different tripanosomatidea flagellates, is presented in a complete follow-up since insect hatches from the egg up to the last molt in the fifth instar stage. The detailed description of the morphological changes which occur in each instar as well as careful measurements evaluating its size increase have been analyzed by stereomicroscopy, phase contrast, dark field, and oblique illumination, in order to optimize the observations as well the photographic register of gonad morphology and structure. The analysis was performed on gonad specimens obtained from broods no less than twenty (20) nymph bugs, reared at constant temperature and fed-up regularly. According to the results of our study we can assert that gonad differentiation takes place in early phases of the insect development. Such is the case that first instars nymph's present absolutely and easily recognizably male and female gonads. From the third instar on beside the filament region, the three zones in each ovariole body is distinguished, a differentiation that is more noticeable during the fourth instar where a definite organization is present at the vitelarium. Such a clear cut zone development continues intensively during the fifth instar. Finally at the end of such fifth nymph stage and when the last molt toward adults is prepared, clear signs of ovariole maturation take place since oocytes in early vitelogenesis are found.